ELEMENTS OF INTERDISCIPLINARY CONNECTIONS IN TEACHING PHYSICS - Mamatkulov Bakhodir Khatamovich (Uzbekistan Open Conference, 2025)
The object of study in natural sciences - such as physics, biology, and biophysics - includes both material and immaterial aspects of nature. When these disciplines are taught, their concepts and laws complement each other. This article is devoted to a partial consideration of the stated issue.
Keywords: natural science; physics; biology; biosphere; cell; mechanics; electricity; blood; velocity; X-rays; treatment